Activity of Isoxazole substituted 9-aminoacridines against SARS CoV-2 main protease for COVID19: A computational approach - Kalirajan, Rajagopal; Gowramma, Byran; Gomathi, Swaminathan; Vadivelan, Ramachandran (Jordan Journal of Pharmaceutical Sciences, 2021)
Coronavirus Disease 2019 (COVID-19), a life-threatening viral disease affected first in china and quickly spread throughout the world in early 2020. So many scientists are rushing to discover novel drugs and vaccines against the coronavirus, and treatments for COVID-19.In the present article, in-silico studies have been performed to explore the binding modes of Isoxazole substituted 9-aminoacridines(1a-x) against SARS CoV-2 main protease (PDB id - 5R82) targeting corona virus using Schrodinger suit 2019-4. The docking studies are performed by Glide module, in-silico ADMET screening was performed by qik prop module and the binding energy of ligands was calculated using PRIME MM-GB/SA module. From the results, Isoxazole substituted 9-aminoacridines like 1n,f,c,k,h,a,e,g,b,d are significantly active against SARS CoV-2 main protease with Glide score more than -5.5 when compared with currently recommended drug for COVID19 Hydroxy chloroquine (G score -5.47) and Co crystallized ligand CID_24701445 (G score -4.4). The docking results of the compounds exhibited similar mode of interactions with COVID19 and the residues THR24, THR25, THR26, SER46, MET49, HIE41, GLN189, ARG189, ASP187, MET168, HIE164, ASN142 and GLY143 play a crucial role in binding with ligands.